Parental sublethal insecticide exposure prolongs mating response and decreases reproductive output in offspring. Issue 7 (16th May 2019) - Müller, Thorben; Römer, Clara Isis; Müller, Caroline
Abstract: Insecticide usage is steadily increasing, implying an ongoing threat of sublethal exposure for non‐target organisms in habitats close to farmland. The exposure to low insecticide doses is often associated with a fitness decline in affected organisms. We determined the effects of exposure to the pyrethroid lambda‐cyhalothrin, at a concentration 20 times lower than the LC50, on the cuticle surface profile containing mating cues, the mating and aggression behaviour and fitness consequences for a beetle species ( Phaedon cochleariae Fabricius), which faces agropollutants when occurring close to farmland. Traits were investigated in the insecticide‐exposed parental generation, and carry‐over effects into their unexposed offspring were studied. In both the parental and the offspring generation, the chemical surface profile was unaffected by the insecticide exposure. Nevertheless, insecticide exposure and carry‐over effects decreased male mating acceptance of females in no‐choice situations. A reduced acceptance of insecticide‐exposed females may be related to changes in specific chemical surface cues, because males attempted to mate more readily with dummies treated with surface extracts of control females than of insecticide‐exposed females. Moreover, females became more aggressive in dual‐choice situations towards other females in the presence of an insecticide‐exposed compared to an unexposed male, potentially due to neuronal dysfunctions. Thus, both intersexual (chemical) communication during mating and intrasexual communication were altered in response to insecticide exposure. Insecticide‐exposed parents and their offspring suffered from a decreased reproductive output, likely due to direct toxic effects or constraints induced by detoxification processes. The carry‐over effects might be mediated by a parental insecticide transfer or insecticide‐induced heritable epigenetic changes involved in detoxification processes. Synthesis and applications . This study demonstrates that sublethal insecticide exposure can have far‐reaching consequences on (non‐target) herbivores. These results have implications for population dynamics and, ultimately, for ecological communities, as insects are highly important members of food chains. Therefore, long‐term effects of short‐term insecticide exposure should be considered in the evaluation of pesticides and the discussion about pesticide usage in agriculture. Abstract : This study demonstrates that sublethal insecticide exposure can have far‐reaching consequences on (non‐target) herbivores. These results have implications for population dynamics and, ultimately, for ecological communities, as insects are highly important members of food chains. Therefore, long‐term effects of short‐term insecticide exposure should be considered in the evaluation of pesticides and the discussion about pesticide usage in agriculture.